OD DEKRETU Z 24 KWIETNIA 1952 R. O ZNIESIENIU FUNDACJI DO USTAWY Z 6 KWIETNIA 1984 R. O FUNDACJACH. PRZEŁOM CZY KONTYNUACJA? RZECZ O FUNKCJONOWANIU WYZNANIOWYCH FUNDACJI DOBROCZYNNYCH W PRL - Szymański, Andrzej (Zeszyty Prawnicze, 2016)
FROM DECREE OF 24TH APRIL 1952 ON ABOLITION OF FOUNDATIONS TO LAW OF 6TH APRIL 1984 ON FOUNDATIONS. A BREAKTHROUGH OR CONTINUATION? MATTER ABOUT FUNCTIONING OF RELIGOUS CHARITY FOUNDATIONS IN PEOPLE’S REPUBLIC OF POLAND Summary The author makes legal evaluation of the process of foundation liquidation on grounds of a decree of 24th April 1952; he ilustrates his deductions by concrete examples, taken from archival search. He also shows actions of Episcopate of Poland, aiming at establishment of Agricultural Foundation which actually resulted in passing by the Parliament of People’s Republic of Poland of an act concerning foundations of 6th April 1984, restoring this institution to the Polish legal order. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />